Vocational Teacher Training –Modeling, Professional Vocabulary Development, Connecting Subjects - Nagyné Kondor, Rita (International Journal of Engineering and Management Sciences, 2024)
Vocational Teacher Training Programmes provide teachers of Vocational Education and Training schools. University of Debrecen Faculty of Engineering offers Vocational Teacher Training in five specializations, in form of cooperative training. The company specialists participating in the training teach prospective vocational teachers with modern professional knowledge. The aim of this article is to summarize the pedagogical experiences of the prospective vocational teachers, based on the content analysis of their lesson plans. The investigation focuses on prospective vocational teachers’ examples of modeling, professional vocabulary development and connections between subjects from their practical pedagogical training in Vocational Education and Training schools.